Information Competences and Academic Achievement: A Dataset - Kohler-Casasempere, J; Gonzalez-Ibanez, R (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
Information literacy (IL) is becoming fundamental in the modern world. Although several IL standards and assessments have been developed for secondary and higher education, there is still no agreement about the possible associations between IL and both academic achievement and student dropout rates. In this article, we present a dataset including IL competences measurements, as well as academic achievement and socioeconomic indicators for 153 Chilean first- and second-year engineering students. The dataset is intended to allow researchers to use machine learning methods to study to what extent, if any, IL and academic achievement are related. Dataset: The dataset is available in the Mendeley Data repository. Doi: http://dx.doi.org/10.17632/7r5fnrhyky.1. Dataset License: The license under which the dataset is made available is CC-BY 4.0. © 2023 by the authors.